Pengaruh lagu Bahasa Jawa Terhadap Sopan Santun Berbicara Pada Anak Usia 5-6 Tahun - Suratiyah, Suratiyah; Kurniawati, Henie; Fadhilah, Iskhulatin; Tunggal Dewi, Fitria Cipta Hadi (Jurnal Anak Usia Dini Holistik Integratif (AUDHI), 2024)
This research aims to determine the influence of Javanese songs on speaking politeness in children aged 5 to 6 years at Kindergarten Pertiwi 2 Dukuhwaluh. The research method used is a quantitative field study using a pre-experimental design. The data collection methods used by researchers are observation, questionnaires, interviews and documentation. Survey instruments or questionnaires are validated by expert assessors. Data analysis carried out was normality testing and hypothesis testing using IBM SPSS Statistics. The following results were obtained: The average score before and after the application of Javanese Songs increased from 23 to 31.11, namely with a percentage increase of 35%; The significance value between the pretest results and the posttest results is 0.001, which means there is a very strong relationship, so Ho is rejected and Ha is accepted. This shows that there is a difference in scores before and after the implementation of the Javanese song; The correlation value between the pretest results and the posttest results is 0.782, which is high, namely close to 1. This means that Javanese songs influence speaking manners in early childhood class B at Kindergarten Pertiwi 2 Dukuhwaluh.Keywords - early childhood, Javanese songs, speaking manners